THE IMPLICATIONS OF TRANSACTION COSTS FOR SALT FARMERS' INDEPENDENCE IN PESANGGRAHAN VILLAGE, KWANYAR DISTRICT, BANGKALAN REGENCY - Kusairi Kusairi; Umar Burhan; Asfi Manzilati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Transaction costs include negotiation, the cost of doing every exchange transaction and usually occur outside the production costs. Transaction costs arise because of the inability to meet the requirements of the salt farmers in making passes. This study aims to identify the cost implications of the independence transksi salt farmers in the Village Pesanggrahan District Kwanyar Bangkalan. The research method in this study is a qualitative method of data collection techniques on interviews and field notes. This study has two types of key informants and informant informant supporters. Results from this study is the existence of transaction costs initiated by salt farmers who do not have passes. Letters road normally used in order to sell directly to the salt production salt factory. The transaction costs in the form of rental fees permit to the owner of the letter. It starts from the farmers who decide to execute contract so that all circuit buying and selling going on striving to independence salt farmers.